2006
DOI: 10.2319/100605-351
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Laceback Ligatures on Maxillary Canine Retraction

Abstract: Objective: To evaluate the effects of laceback ligatures on canine distalization during the leveling and aligning stage and to compare the effectiveness of laceback ligatures with that of superelastic NiTi closed coil springs. Materials and Methods: Fifteen subjects were included in this study. Fixed orthodontic treatment was planned with the extraction of first premolars to solve crowding in upper and/or lower arches. Stainless steel direct-bonding Roth brackets (0.022-inch) were used. For canine distalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
0
20
0
2
Order By: Relevance
“…35,36 At all three time intervals of the study, salivary leptin concentrations were higher in overweight individuals when compared with normal weight individuals. These results were consistent with previous studies, which suggested that serum leptin levels were higher in overweight individuals as compared with normal weight individuals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…35,36 At all three time intervals of the study, salivary leptin concentrations were higher in overweight individuals when compared with normal weight individuals. These results were consistent with previous studies, which suggested that serum leptin levels were higher in overweight individuals as compared with normal weight individuals.…”
Section: Discussionmentioning
confidence: 96%
“…A distal force was applied to the maxillary right canine using active lacebacks, and the force was standardized by giving an equal number of turns (five turns) for each subject. 35,36 An upper alginate impression was made for all subjects before and 3 months after appliance placement, and models were poured using type IV dental stone (Orthokal, Kalabhai Company). The distance from the mesial contact point of the right maxillary canine to that of the second premolar was measured from the study models before and after force application using an electronic digital caliper, and the difference between the two measurements was recorded as the net distal movement of the right maxillary canine over 3 months.…”
Section: Application Of Force and Calculation Of Rate Of Tooth Movementmentioning
confidence: 99%
“…12,13 Studies have focused on how to produce a more bodily canine movement and examined whether new technologies can make any difference in decreasing the distalization of the canine and overall treatment time. [32][33][34][35][36] A previous study by Ammar et al 25 showed…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the laceback ligatures are effective for canine distalisation [8]. In a randomized controlled clinical trial investigating the effectiveness of the laceback ligatures showed no statistical or clinical difference in the anteroposterior or vertical position of the lower labial segment or in the relief of labial segment crowding and the use of laceback ligatures creates a statistically and clinically significant increase in the loss of posterior anchorage, through mesial movement of the lower first molars [9].…”
Section: Discussionmentioning
confidence: 99%